Analisis Performansi Turbin Angin Poros Horisontal Model Double Rotor Contra Rotating dengan Posisi Rotor Saling Berhimpitan - Fredrikus M. Bere; Verdy Ariyanto Koehuan; Jahirwan Ut Jasron (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2015)
Abstract The contra rotating wind turbine is a horizontal axis turbine which has two shaft rotating in opposite directions on the same axis, and it can work at low wind speeds. In general, the performance of the wind turbine are affected by several factors, which is the aerodynamics shape of turbine, the numbers of blade and the selection angle of blade. In this study, conducted by determining the variation of angle on the blade and the blade angle used in the study is 0o, 5o, and 10o, on the two rotors with diameter of front rotor is 0.50 meters and the rear rotor is 0.30 meters, with the position of the rotor blade is coincident with each other. The purpose of this study, is to determine the effect of blade angle variation on the turbine rotation (rpm), torque (T), the power coefficient (Cp), torque coefficient (Cq) and the efficient of the turbine at any wind speeds variations. On the graph relation of blade angle on the shaft rotation, turbine rotation riding known to along with the addition of angle of the blade. The speed of wind is very affect on the output or mechanical power and power coefficient. On the blade angle 0o with wind speed at 4.03 m/s, the power can be generate is 3.013 Watt, and for blade angle 10o with wind speeds 6.08 m/s, the power can be generate is 8.217 Watt. The lowest rotation of rotor without loading is 702 rpm at the wind speeds on 4.03 m/s with angle of blade 0o, the highest rotation of rotor is 1484 rpm on the wind speeds 6.08 m/s with angle of blade 10o. From the graph of analysis data can be seen , with change of angle blade on wind turbine horizontal shaft contra rotating models, power coefficient (Cp) generated of turbine activity increases with increased of angle, with Cp maks 0.718 for angle 10o, maximum efficiency an generated reach out 71.8%.